628. The Role of the Advanced Practice Provider in Infectious Disease: Opportunities for Growth. (31st December 2020) - Yoke, Leah H; Yoke, Leah H; Beieler, Alison M; Beieler, Alison M; Liu, Catherine; Pergam, Steven A; Wald, Anna; Wald, Anna; Dhanireddy, Shireesha; Dhanireddy, Shireesha
Abstract: Background: Advanced Practice Providers (APPs), including nurse practitioners and physician assistants, provide high quality medical care in multiple specialties by extending the physician workforce. However, within the Infectious Disease (ID) specialty, their demographics, areas of practice, and experience are not well described. To better understand this key group, we examined APP years of experience in ID, primary practice settings, and perceived practice barriers from the APP perspective. Methods: We created a survey using REDCap which was distributed between 12/1/2019-1/31/2020 to APPs practicing in ID by social media, direct emails to key stakeholders, and online Infectious Disease Society of America (IDSA) community forums. Results: Ninety-three APPs responded to the posted survey from across the US (figure 1). Most respondents (45 [49%]) had between 2-9 years of overall experience as an APP, while 14 (15%) between 10-15 years, and 24 (26%) had >16 years of experience. Experience specifically as an ID APP varied, with the majority (56%) having 2-9 years of experience and 25% reporting >16 years of experience as an APP. Although over half of the respondents worked in an outpatient adult ID clinic, they also practiced in diverse settings and within multiple ID sub-specialties (figure 2). The other most common areas of practice included inpatient adult ID, HIV care, and outpatient parental antimicrobial therapy programs. Limited formalized ID education and misconceptions about APP scope of practice were perceived barriers to practicing in ID (figure 3). Lack of recognition as a peer amongst physician colleagues was also identified as a practice barrier. Advanced Practice Provider Survey Response by Region Advanced Practice Provider ID Practice Areas Perceived Advanced Practice Provider Barriers Conclusion: Our survey results demonstrate that the APP ID workforce is an experienced provider group, both in terms of total years as an APP and years exclusively in ID, working in a large variety of ID settings in a number of geographic locations. Creation of specific and directed ID educational opportunities, along with collaborating physician support and inclusion, are identified as significant areas of improvement. The establishment of APP-specific training programs and educational courses will create more opportunities for APPs and further expand the ID workforce. Disclosures: Steven A. Pergam, MD, MPH, Chimerix, Inc (Scientific Research Study Investigator)Global Life Technologies, Inc. (Research Grant or Support)Merck & Co. (Scientific Research Study Investigator)Sanofi-Aventis (Other Financial or Material Support, Participate in clinical trial sponsored by NIAID (U01-AI132004); vaccines for this trial are provided by Sanofi-Aventis)